Uji Empiris Reformulasi Kondisi Marshall-Lerner untuk Kasus Ekspor dan Impor Manufaktur di Indonesia - Yudotaruno, Taukhid; Falianty, Telisa Aulia (UI Scholars Hub, 2016)
This study aims to examine the condition of Marshall-Lerner regard to the simultaneous relationship of export and import of Indonesia’s manufacturing sector. This simultaneous relationship occurs due to Indonesia’s manufacturing industry is part of the global production network as of its export products containing imported intermediate inputs. SVAR is using to analyze the simultaneous relationship between variables with their own variables and other variables in the past. Its due to changes in export and import values do not immediately occur at the same time with changes in exchange rates. Empirical results shows that by taking into account the simultaneous relationship of exports and imports, Marshall- Lerner conditions still met.